The Common Space in Southeast Asian Higher Education - Antonio Lim, Miguel; Sisavath, Soubin; Elepaño, Mark (International Higher Education, 2025)
This article examines the promise and challenges of the Common Higher Education Space in Southeast Asia following the 2024 Joint Declaration signed by ASEAN and SEAMEO. While the declaration marks a key milestone in regional cooperation, persistent disparities in resources, readiness, and regulatory alignment reveal a collective action problem. The article argues that sustained political will, coordinated implementation, and inclusive engagement are essential for turning regional ambition into meaningful, long-term impact.